2018
DOI: 10.1371/journal.pone.0198967
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of WNT1-inducible signaling pathway protein 1 polymorphism on hepatocellular carcinoma development

Abstract: BackgroundWNT1-inducible signaling pathway protein 1 (WISP1) is a member of CCN protein family and a downstream target of β-catenin. Aberrant WISP1 expression is associated with carcinogenesis. In the current study, we focused on examining WISP1 single nucleotide polymorphisms (SNPs) to elucidate hepatocellular carcinoma (HCC) clinicopathologic characteristics.Methodology/Principal findingsThe WISP1 SNPs rs2977530, rs2977537, rs2929973, rs2929970, rs62514004, and rs16893344 were analyzed by real-time polymeras… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 50 publications
1
11
0
Order By: Relevance
“…WISP1 polymorphisms have been identified in various cancers, including breast cancer [ 13 ], urothelial cell carcinoma [ 14 ], hepatocellular carcinoma [ 15 ], oral squamous cell carcinoma [ 16 ], lung cancer [ 17 ], and uterine cervical cancer [ 18 ], but data are scant as to the involvement of WISP1 polymorphisms in gastric cancer. As far as we are aware, our study is the first to investigate the distributions of the rs2929973, rs7843546, and rs10956697 SNPs and their associations with the development of gastric cancer in a Guangxi Chinese population.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…WISP1 polymorphisms have been identified in various cancers, including breast cancer [ 13 ], urothelial cell carcinoma [ 14 ], hepatocellular carcinoma [ 15 ], oral squamous cell carcinoma [ 16 ], lung cancer [ 17 ], and uterine cervical cancer [ 18 ], but data are scant as to the involvement of WISP1 polymorphisms in gastric cancer. As far as we are aware, our study is the first to investigate the distributions of the rs2929973, rs7843546, and rs10956697 SNPs and their associations with the development of gastric cancer in a Guangxi Chinese population.…”
Section: Discussionmentioning
confidence: 99%
“…The WISP1 gene consists of five exons and four introns located on chromosome 8q24.1 to 8q24.3, and it has been shown to be highly polymorphic [ 13 ]. Several clinical studies have indicated a significant association between WISP1 polymorphisms and various cancers, such as breast cancer [ 14 ], urothelial cell carcinoma [ 15 ], hepatocellular carcinoma [ 16 ], oral squamous cell carcinoma [ 17 ], lung cancer [ 18 ] and uterine cervical cancer [ 19 ]. Up until now, to our knowledge, no study has established a connection between WISP1 genetic polymorphisms and gastric cancer.…”
Section: Introductionmentioning
confidence: 99%
“…The specimens from oral cancer patients and normal controls were further isolated from the genomic DNA with QIAamp DNA blood mini kits. From the whole blood specimens, the buffy coats were isolated and then the genomic DNA was extracted according to the protocol in previous studies [24][25][26]. The MACC1 rs3095007 (assay IDs: C__27452671_10), rs1990172 (assay IDs: C___2632417_10), rs4721888 (assay IDs: C__27869756_10), rs975263 (assay IDs: C___2632422_20), and rs3735615 (assay IDs: C__27489506_10) SNP was carried out by using the TaqMan™ Genotyping Master Mix on the ABI StepOne™ Real-Time PCR System (Applied Biosystems, Foster City, CA, USA), and the genotypes were determined using SDS software (version 3.0) (Applied Biosystems, Foster City, CA, USA) as in the previous studies [21,27].…”
Section: Macc1 Snp Selection and Dna Extraction And Genotypingmentioning
confidence: 99%
“…The genomic DNA extraction was performed with QIAamp DNA blood mini kits. The buffy coats extracted from the whole blood specimens were used for DNA extraction, and the DNA extraction assay was performed according to previous described [28][29][30]. Extracted DNA was dissolved in Tris-EDTA (TE) buffer and was applied as DNA template in the following process of polymerase chain reactions (PCRs).…”
Section: Sample Preparation and Dna Extractionmentioning
confidence: 99%